BIMBINGAN MARINASI DAN OTAK-OTAK IKAN UPAYA NILAI TAMBAH DAN PEMBERDAYAAN MASYARAKAT PESISIR DI KELURAHAN TONDONGGEU - Nur Asizah, Nur Asizah; Daeng Siang, Roslinda; Nur Afiat, Muhammad; Ilyas, Ilyas; Muslim, Caesar; Tajuddin, Tajuddin (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Coastal communities at Tondonggeu Village face limitations in post-harvest fish processing, resulting in low added value for seafood products. To address this, this community service program provided training in marinated fish and fish otak-otak processing technology, business management mentoring, and digital marketing strategies. A total of 30 participants (90% women) participated in the practical and theoretical training. Evaluation using a Likert-based questionnaire (1–5) showed an average score of 4.1 for the training implementation, and participants reported significant improvements in technical skills, hygiene understanding, and entrepreneurial motivation. These results indicate that a participatory and capacity-based approach can strengthen local economic empowerment and support the formation of small businesses based on fishery products. Further mentoring for packaging, business licensing, and marketing expansion is recommended.